1989
DOI: 10.1002/j.1460-2075.1989.tb08354.x
|View full text |Cite
|
Sign up to set email alerts
|

vav, a novel human oncogene derived from a locus ubiquitously expressed in hematopoietic cells.

Abstract: A novel human oncogene, designated vav, was generated by a genetic rearrangement during gene transfer assays. The vav oncogene directs the synthesis of a 3.0 kb mRNA from which we isolated a 2.8 kb‐long complementary DNA copy. Nucleotide sequence analysis of this vav oncogene cDNA clone revealed that its 5′ 167 bp were derived from pSV2neo DNA cotransfected as a selectable marker during gene transfer. The remaining 2597 bp were unrelated to genes included in current data banks, indicating that the vav oncogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
395
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(407 citation statements)
references
References 38 publications
(26 reference statements)
5
395
1
Order By: Relevance
“…Both cleavage sites are located within the acidic domain and chop o the N-terminal part containing a CH domain (Katzav, 1995). In this context it is noteworthy that the oncogenic form of Vav1 arises from the deletion of 67 N-terminal amino acids from Vav1 and induces tumors in nude mice (Katzav et al, 1989;Coppola et al, 1991). Although this N-terminal truncation of Vav1 induces its oncogenic activity, the ability to induce NF-AT-dependent transcription is reduced (Wu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cleavage sites are located within the acidic domain and chop o the N-terminal part containing a CH domain (Katzav, 1995). In this context it is noteworthy that the oncogenic form of Vav1 arises from the deletion of 67 N-terminal amino acids from Vav1 and induces tumors in nude mice (Katzav et al, 1989;Coppola et al, 1991). Although this N-terminal truncation of Vav1 induces its oncogenic activity, the ability to induce NF-AT-dependent transcription is reduced (Wu et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This 95 kDa protein displays a wide variety of structural motifs including a N-terminal calponin homology (CH) domain, an acidic domain (AD), a Dbl-homology (DH) domain, a putative bipartite nuclear localization signal (NLS), a pleckstrin homology (PH) domain, a cysteine-rich domain (CR) and one SH2-domain anked by two SH3 domains (Romero and Fischer, 1996). Its expression is restricted to cells of haematopoietic origin (Katzav et al, 1989). Targeted gene disruption revealed the importance of Vav1 for receptor-mediated proliferation and TCR-mediated positive selection (Fischer et al, 1995;Tarakhovsky et al, 1995;Zhang et al, 1995;Turner et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The vav gene was ®rst identi®ed by virtue of its oncogenic activation during the course of gene transfer assays (Katzav et al, 1989). Its normal allele, the vav proto-oncogene, encodes a 95 kDa polypeptide that harbors a complex array of structural domains, including leucine-rich, acidic, Dbl-homology (DH), pleckstrin-homology (PH), cysteine-rich, SH3 and SH2 domains (for a review, see Bustelo 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The important role of this gene during mitogenic and ontogenic processes was demonstrated by both cell biology and genetic experiments. Thus, it has been shown that Vav can induce high levels of morphological transformation in rodent ®broblasts after deletion of N-terminal sequences (Katzav et al, 1989;Coppola et al, 1991). Moreover, disruption of the vav locus by homologous recombination techniques results in severe signaling defects of primary antigen receptors, leading to abnormal lymphocyte proliferation and lymphocytopenia (Fisher et al, 1995;Tarakhovski et al, 1995;Zhang et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that both the GEF activity and the transforming activity of the Dbl protein was localized to a 240 amino acid motif between residues 498 and 738 in the protein (Hart et al, 1994). An emerging group of proteins conferring homology to this 240 amino acid motif in the Dbl oncogene has been identi®ed including Vav (Katzav et al, 1989), Ect-2 (Miki et al, 1993), Lbc (Toksoz and Williams, 1994), Lfc (Whitehead et al, 1995), Tim (Chan et al, 1994), Tiam (Habets et al, 1994), Cdc24 (from Saccharomysis cerevisia; Drubin, 1991), the breakpoint cluster region protein (Bcr; Hariharan and Adams, 1987), and the mammalian ras guanidine releasing factor (Shou et al, 1992).…”
mentioning
confidence: 99%